Prenatal Alcohol Exposure and Congenital Heart Defects: A Meta-Analysis - Yang, Jiaomei; Qiu, Huizhen; Qu, Pengfei; Zhang, Ruo; Zeng, Lingxia; Yan, Hong (PLOS ONE, 2015)
Background There are still inconsistent conclusions about the association of prenatal alcohol drinking with congenital heart defects (CHDs). We conducted this meta-analysis to investigate the association between prenatal alcohol exposure and the risk of overall CHDs and the CHDs subtypes. Methods Case-control and cohort studies published before March 2015 were searched through PubMed and Embase. Two authors independently extracted data and scored the study quality according to the Newcastle-0ttawa Scale. The pooled ORs and 95%CI were estimated using the random-effects model and heterogeneity was assessed by the Q test and I2 statistic. Results A total of 20 studies were finally included. The results provided no evidence of the association between prenatal alcohol exposure and the risk of overall CHDs (OR = 1.06, 95%CI = 0.93–1.22), ventricular septal defects (VSDs) (OR = 1.04, 95%CI = 0.86–1.25), or atrial septal defects (ASDs) (OR = 1.40, 95%CI = 0.88–2.23). However, prenatal alcohol drinking was marginally significantly associated with conotruncal defects (CTDs) (OR = 1.24, 95%CI = 0.97–1.59) and statistically significantly associated with d-Transposition of the Great Arteries (dTGA) (OR = 1.64, 95%CI = 1.17–2.30). Moreover, both prenatal heavy drinking and binge drinking have a strong association with overall CHDs (heavy drinking: OR = 3.76, 95%CI = 1.00–14.10; binge drinking: OR = 2.49, 95%CI = 1.04–5.97), and prenatal moderate drinking has a modest association with CTDs (OR = 1.35, 95%CI = 1.05–1.75) and dTGA (OR = 1.86, 95%CI = 1.09–3.20). Conclusions In conclusion, the results suggested that prenatal alcohol exposure was not associated with overall CHDs or some subtypes, whereas marginally significant association was found for CTDs and statistically significant association was found for dTGA. Further prospective studies with large population and better designs are needed to explore the association of prenatal alcohol exposure with CHDs including the subtypes in specific groups.